2021
DOI: 10.1186/s12959-021-00260-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of anticoagulation using low molecular-weight heparin during catheter-directed thrombolysis for lower extremity deep venous thrombosis

Abstract: Background The optimal anticoagulant scheme during catheter-directed thrombolysis (CDT) for deep venous thrombosis (DVT) remains unknown. This study was performed to evaluate the feasibility of anticoagulation therapy using low molecular-weight heparin (LMWH) during CDT for DVT. Methods The clinical data of DVT patients who underwent CDT during the past six years was retrospectively collected and reviewed. Patients were divided into therapeutic-dos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The search yielded 4,168 references and 46 met the eligibility criteria for inclusion in this review 5 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 reporting 49 CDT protocols ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The search yielded 4,168 references and 46 met the eligibility criteria for inclusion in this review 5 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 reporting 49 CDT protocols ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Physical pressure therapy includes the use of elastic stockings and intermittent pneumatic compression devices. The treatment plan for PCDT at our center was detailed in our previous study (22). The patients were treated with LMWH twice daily before and after PCDT.…”
Section: Clinical Treatmentmentioning
confidence: 99%
“…Studies have shown that delivering the UK can effectively enhance the efficacy of thrombolytic therapy, making it a promising clinical application for the treatment of DVT. 27 Under normal conditions, the half-life of urokinase is usually short, about a few hours. This means that the activity of urokinase decreases rapidly over a short period of time.…”
Section: Introductionmentioning
confidence: 99%